solve y(1+2xycosx^2-2xy)dx+(sinx^2-x^2)dy=0
NOTE: I asked for cosx^2 is cos(x2) or cos2x at the work start but no answer.
Solution
y(1+2xycos2x-2xy)dx + (sin2x-x2)dy = 0
Dividing by (sin2x-x2)dx we will get
dy/dx = -y(1+2xycos2x-2xy)/(sin2x-x2) =
= y(2xysin2x - 1)/(sin2x-x2) = -y/(sin2x-x2)+ 2x y2 sin2x /(sin2x-x2)
So y’+ y/(sin2x-x2) = [2x sin2x /(sin2x-x2)] y2
It is Bernoulli differential equation
y’ + p(x)y = q(x)y2
with p(x) = (sin2x-x2)-1 , q(x) = 2x sin2x /(sin2x-x2)
Divide this by y2 .
y-2y’ + p(x)y-1 = q(x)
The substitution and derivative that we’ll need here is
v=y−1, v′=−y−2y′
With this substitution the differential equation becomes
v’ – p(x)v = -q(x)
Let m(x) = exp(-∫p(x) dx) = exp(-∫(sin2x-x2)-1 dx)
Multiplying last equation m(x) we’ll get
(m(x)v)’ = -m(x) q(x)
Integrating this ∫ (m(x)v)’dx = -∫m(x) q(x)dx and so
v = 1/y = -[m(x)]-1∫ m(x) q(x)dx - C
And y = -{[m(x)]-1∫ m(x) q(x)dx + C}-1
Finally
y = -{[ exp(-∫(sin2x-x2)-1 dx)]-1∫ exp(-∫(sin2x-x2)-1 dx)*2x sin2x /(sin2x-x2) dx + C}-1
or
"y(x)=\\ -\\{ \\ [ exp(-\\int \\frac{dx}{sin^2x-x^2} ) \\ ]^{-1} \n\\int exp(-\\int \\frac{dx}{sin^2x-x^2} ) \\frac{2x sin^2x}{sin^2x-x^2} dx +C \\}^{-1}"
Comments
Leave a comment